2014
DOI: 10.1128/aac.02475-13
|View full text |Cite
|
Sign up to set email alerts
|

Study of Macrophage Functions in Murine J774 Cells and Human Activated THP-1 Cells Exposed to Oritavancin, a Lipoglycopeptide with High Cellular Accumulation

Abstract: Oritavancin, a lipoglycopeptide antibiotic in development, accumulates to high levels in the lysosomes of eukaryotic cells. We examined specific functions of macrophages (phagocytic capacity, lysosomal integrity, metabolic activity, and production of reactive oxygen species [ROS]) in correlation with the cellular accumulation of the drug, using J774 mouse macrophages and THP-1 human monocytes differentiated into macrophages using phorbol 12-myristate 13-acetate. Oritavancin did not affect Pseudomonas aeruginos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 53 publications
(69 reference statements)
1
12
0
2
Order By: Relevance
“…For extracellular infections, homogenization of the tissue dilutes drugs that are mainly located in the extracellular compartment, which may lead to an underestimation of the active concentration of drug (17). Oritavancin is known to accumulate intracellularly within macrophages (18,19). In this case, total oritavancin concentrations in tissue may be overestimated if the infection is extracellular and underestimated if it is intracellular.…”
Section: Discussionmentioning
confidence: 92%
“…For extracellular infections, homogenization of the tissue dilutes drugs that are mainly located in the extracellular compartment, which may lead to an underestimation of the active concentration of drug (17). Oritavancin is known to accumulate intracellularly within macrophages (18,19). In this case, total oritavancin concentrations in tissue may be overestimated if the infection is extracellular and underestimated if it is intracellular.…”
Section: Discussionmentioning
confidence: 92%
“…Moreover, this effect was reversible upon drug removal [76]. When the exposure [173] of cells was limited to drug amounts for which cellular concentrations were of the same order of magnitude as those measured in patients, no specific sign of intoxication of macrophages was evidenced, including with respect to phagocytic or killing capacities or oxidant species production [77,78]. Telavancin also caused cellular lipidosis, but to a much lower extent than oritavancin, related to its lower cellular accumulation [79].…”
Section: In Vitro Models Of Persistent Infectionsmentioning
confidence: 95%
“…In vitro studies have indeed demonstrated the deposition of undigested lipidic material within lysosomes of cells exposed to the drug continuously for 1-3 days [76], but only in conditions generating intracellular concentrations well above those measured in macrophages from patients treated with the drug [77]. Moreover, this effect was reversible upon drug removal [76].…”
Section: In Vitro Models Of Persistent Infectionsmentioning
confidence: 96%
“…We believe that this can be over the best solution here is using advanced technology and a multidisciplinary approach. Recently, great advances have been made in the field of abiotic membrane-active polymers that can coat cell membranes whilst maintaining cell viability 98 . These polymers can be "decorated" with an opsonin to enhance encapsulation; the polymer can be deconstructed by e.g.…”
Section: Additional Factors To Considermentioning
confidence: 99%